Colombian Sustainability Perspective on Fused Deposition Modeling Technology: Opportunity to Develop Recycled and Biobased 3D Printing Filaments (2023)
In the context of the preservation of natural resources, researchers show a growing interest in developing eco—friendly materials based on recycled polymers and natural fiber biocomposites to minimize plastic and agroindustrial waste pollution. The development of new materials must be integrated within the circular economy concepts to guarantee sustainable production. In parallel, fused deposition modeling, an additive manufacturing technology, provides the opportunity to use these new materials in an efficient and sustainable manner. This review presents the context of plastics and agro-industrial fiber pollution, followed by the opportunity to give them added value by applying circular economy concepts and implementing these residues to develop new materials for the manufacture of fused deposition modeling 3D printing technique feedstock. Colombian perspective is highlighted since 3D printing technology is growing there, and Colombian biodiversity represents a high reservoir of materials. Also, recycling in Colombia promotes compliance with the 2030 Agenda and the Sustainable Development Goals.